Meta-Religion - Ismail Raji al Faruqi (International Institute of Islamic Thought, 1986)
I. FIVE STAGES OF THE STUDY OF RELIGION Religion has been defined as the experience of a reality that is assumed to be ultimate as well as personal, thus making the experience an encounter? This modem definition is not without merit; for in religion, the object of experience is indeed regarded as ultimate and in most cases as a commanding person. It is inadequate, however, because it does not specify the experience. In order to fulfill the meaning of religion, one has to add that the ultimate reality experienced must be apprehended and understood, expressed and proclaimed, its commandments acquiesced in and responded to with individual and collective action. Religion therefore is the most important constituent of man’s humanity. First, it includes the vision of reality and the articulation of that vision, its expression in concepts for the understanding and percepts for the imagination. This vision and its expression have constituted most of man’s intellectual output throughout history. Second, it includes acquiescence in the commanding nature of Ultimate Reality and actualization of its commandments, and hence includes most of man’s subjective conditions and personalist values. Third, since the commandments have as their goal the actualization of the highest good, religion includes most or all of man’s action as it relates to ...